La Legge Nuova e la conformità con la Volontà di Dio - Mestre, Alberto (Alpha omega, 2020)
While the theological virtue of charity is the swiftest way to conform the human will with the Divine Will, this conformity cannot be achieved without the intervention of the Holy Spirit. This article aims to show that the Holy Spirit is the main protagonist of the conformity of those wills. Moreover, it is thanks to the deepening of the doctrine of the New Law that the objective of Christian life, which is assimilation to Christ, is achieved.